2010
DOI: 10.1177/0022002710371666
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Terrorism through the Rule of Law?

Abstract: The question of whether democratic institutions facilitate terrorist activities is a controversial one in current scientific studies of terrorism. Although the ''rule of law'' is an essential institutional pillar of any mature democracy, its direct effect on domestic and international terrorism remains unexplored. Conceiving democratic rule of law as the coexistence of effective and impartial judicial systems and citizens' recognition of the law as legitimate, the author presents a causal explanation in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 43 publications
8
104
1
2
Order By: Relevance
“…Consistent with Choi (2010) In the second strand, governance is also linked to transnational terrorism in the view that good governance consolidates the legitimacy of a political system by providing a protective shield to both foreigners and citizens on the one hand, as well as nonviolent mechanisms to dispute resolution on the other hand (Choi 2010). Hence, in the light of governance definitions we have clarified above, terrorism is very likely to be limited by, inter alia: (i) a free and fair democratic procedure for the election and replacement of political leaders (political governance); (ii) the formulation and implementation of conducive policies that deliver public commodities to citizens (economic governance) and (iii) sound respect by the State and citizens of institutions that govern interactions between them (institutional governance).…”
Section: Theoretical Underpinningssupporting
confidence: 55%
See 3 more Smart Citations
“…Consistent with Choi (2010) In the second strand, governance is also linked to transnational terrorism in the view that good governance consolidates the legitimacy of a political system by providing a protective shield to both foreigners and citizens on the one hand, as well as nonviolent mechanisms to dispute resolution on the other hand (Choi 2010). Hence, in the light of governance definitions we have clarified above, terrorism is very likely to be limited by, inter alia: (i) a free and fair democratic procedure for the election and replacement of political leaders (political governance); (ii) the formulation and implementation of conducive policies that deliver public commodities to citizens (economic governance) and (iii) sound respect by the State and citizens of institutions that govern interactions between them (institutional governance).…”
Section: Theoretical Underpinningssupporting
confidence: 55%
“…Accordingly, the negative relationship with the rule of law is in accordance with Choi (2010) who has established a negative relationship between democratic rule of law and citizens' willingness and opportunity of resorting to political violence and terrorism as means to resolving conflicts.…”
Section: 1 Nexus With the Literaturementioning
confidence: 78%
See 2 more Smart Citations
“…The advantage in financial development established by Beck et al (2013) has been confirmed within the frameworks educational performance and economic growth by Agbor (2015). In essence, the logic underpinning this classification is that, the institutional web of formal rules, informal norms and enforcement characteristics within a legal system influence how terrorism is fought by means of institutional regimes and government quality (Li, 2005;Choi, 2010;Lee et al, 2013). Classification of countries within this category is based on information from La Porta et al (2008, p. 289).…”
Section: Determination Of Fundamental Characteristicsmentioning
confidence: 99%